1999
DOI: 10.1177/106689699900700308
|View full text |Cite
|
Sign up to set email alerts
|

Mammary Dirofilariasis

Abstract: We report a case of a dirofilariasis manifesting as a breast nodule in a 32-year-old Tunisian woman. It appeared as a relatively well-circumscribed and slightly dense nodule on mammography and was hypoechogenic with enhanced through transmission on ultrasonographic examination. The patient was treated by surgical resection. Histopathologic analysis could identify viable female and male worms as Dirofilaria repens. Dirofilaria is rare in Tunisia and this is the second human case reported. The patient lived all … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 12 publications
0
6
0
Order By: Relevance
“…Sporadic cases of human infection with D. repens have been reported from Nigeria (O'Grady et al, 1962), Senegal (Harant and Brès, 1946), Kenya (Orihel et al, 1997), Tunisia (Chaabouni et al, 1990;Kassar et al, 1990;Ben Said et al, 1995;Mrad et al, 1999) and South Africa (De Meillon and Gillespie, 1962). In the Alexandria area of northern Egypt, Awadalla et al (1998) found a case that they considered 'a possible D. repens', and Antonios and Bayoumy (2002) reported another case, although, confusingly, they described the causative parasite both as the dog heartworm (which is the common name for D. immitis) and, a few lines later, as D. repens.…”
Section: Human Infections With Dirofilaria Repens In Egyptmentioning
confidence: 93%
“…Sporadic cases of human infection with D. repens have been reported from Nigeria (O'Grady et al, 1962), Senegal (Harant and Brès, 1946), Kenya (Orihel et al, 1997), Tunisia (Chaabouni et al, 1990;Kassar et al, 1990;Ben Said et al, 1995;Mrad et al, 1999) and South Africa (De Meillon and Gillespie, 1962). In the Alexandria area of northern Egypt, Awadalla et al (1998) found a case that they considered 'a possible D. repens', and Antonios and Bayoumy (2002) reported another case, although, confusingly, they described the causative parasite both as the dog heartworm (which is the common name for D. immitis) and, a few lines later, as D. repens.…”
Section: Human Infections With Dirofilaria Repens In Egyptmentioning
confidence: 93%
“…In most of the cases a single worm develops, probably because the stimulation of the immune system prevents the development of others [1, 8]. In rare cases the worm may develop to a mature adult [1, 207, 208] and even fertilized worms releasing microfilariae have been described, especially in immunosuppressed patients [1, 8, 42, 146, 209212], which in very rare cases may even reach the bloodstream [213].…”
Section: Human Infectionsmentioning
confidence: 99%
“…In this case, the maximum body width measured approximately 500 μm. Although an extensive review of human infections by D. repens found that female worms were more prevalent than males (Pampiglione and Rivasi 2000), a male and a female worm have been observed in the same nodule (Mrad et al 1999), and also in separate nodules (Fernando et al 2000). In the majority of cases, nodules are located in subcutaneous and subconjunctival tissues, deep dermis and submucosa.…”
Section: Resultsmentioning
confidence: 96%